Peningkatan Kreativitas Tenaga Pendidik Melalui Efikasi Diri Dan Pelatihan - Lia Yulianti; Bibin Rubini; Rais Hidayat; Yuyun Elizabeth Patras (Universitas Pakuan, 2022)
Increasing The Creativity of Educators through Self-Efficiency and TrainingThe purpose of this study was to determine the relationship between self-efficacy and training with the creativity of educators at the Setukpa Lemdiklat Polri Sukabumi. The research population was 149 educators and a sample of 109 educators. Collecting data for each variable studied uses a questionnaire with a rating scale. The data analysis technique uses descriptive statistical analysis techniques and inferential statistical analysis techniques. The results showed: a) there was a positive and significant relationship between self-efficacy and creativity of educators where the correlation coefficient was ry. 1 = 0.358, and the regression equation = 64,494 + 0.627X1. The contribution of self-efficacy to the creativity of educators is 12%, b) there was a significant positive relationship between personality and creativity of educators where the correlation coefficient was ry. 2 = 0.435 and the regression equation = 59.594 + 0.632X2, the contribution of personality to the creativity of educators was 18.2%, and c) there was a significant positive relationship between self-efficacy and personality together with the creativity of educators where the correlation coefficient was R = 0.456 and the regression equation = 79.552 + 0.682.X1 + 1.161.X2. The contribution of self-efficacy and personality together to the creativity of educators is 19.3%.